2014
DOI: 10.1007/s11605-014-2681-3
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Study Evaluating the Development of Bowel Wall Edema During Laparoscopic and Open Visceral Surgery

Abstract: Laparoscopic surgery does not seem to lead to the bowel wall edema observed to occur in open surgery regardless of the degree of intravenous fluid administration, thus supporting its use even in major visceral surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…The functional cause, however, remains an issue of debate. As a potential mechanism, a prospective study by Marjanovic et al found a reduction of postoperative bowel edema in patients undergoing LPD compared to OPD, reducing postoperative impaired bowel movement and peristaltic 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional cause, however, remains an issue of debate. As a potential mechanism, a prospective study by Marjanovic et al found a reduction of postoperative bowel edema in patients undergoing LPD compared to OPD, reducing postoperative impaired bowel movement and peristaltic 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Mögliche Gründe werden aktuell kontrovers diskutiert. Als potenzielle Ursache konnten Marjanovic et al in einer prospektiven Studie eine Reduktion der postoperativen gastrointestinalen Ödembildung bei LPD-Patienten im Vergleich zu OPD-Patienten zeigen, dies führte zu geringeren Einschränkungen von Peristaltik und Darmmotilität 28 .…”
Section: Diskussionunclassified
“…We suspect that the development of bowel wall edema would have contributed to the difference in the incidence of POPF between the two groups. Marjanovic et al showed the beneficial effects of laparoscopic surgery versus open visceral surgery in preventing bowel wall edema [ 30 ] and concluded that prevention of bowel wall edema formation is an advantage of minimally invasive surgery with respect to anastomotic healing. Hiki et al showed that postoperative inflammation is less pronounced after laparoscopic procedures than after open surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeons recognise from experience that the development of bowel wall oedema plays a key role in anastomotic failure. One comparative study evaluated the development of bowel wall oedema during laparoscopic and open visceral surgeries, showing that laparoscopic surgery is associated with lower rates of this finding 33 . The authors concluded that prevention of bowel wall oedema may be one advantage of minimally invasive surgery, as it leads to faster anastomotic healing.…”
Section: Discussionmentioning
confidence: 99%